GIRK Channels as Candidate Targets for the Treatment of Substance Use Disorders - Hiroko Kotajima-Murakami; Soichiro Ide; Kazutaka Ikeda (Biomedicines, 2022)
Substance use disorders (SUDs) are chronic, lifelong disorders that have serious consequences. Repeated substance use alters brain function. G-protein-activated inwardly rectifying potassium (GIRK) channels are expressed widely in the brain, including the reward system, and regulate neuronal excitability. Functional GIRK channels are identified as heterotetramers of GIRK subunits (GIRK1–4). The GIRK1, GIRK2, and GIRK3 subunits are mainly expressed in rodent brain regions, and various addictive substances act on the brain through GIRK channels. Studies with animals (knockout and missense mutation animals) and humans have demonstrated the involvement of GIRK channels in the effects of addictive substances. Additionally, GIRK channel blockers affect behavioral responses to addictive substances. Thus, GIRK channels play a key role in SUDs, and GIRK channel modulators may be candidate medications. Ifenprodil is a GIRK channel blocker that does not have serious side effects. Two clinical trials were conducted to investigate the effects of ifenprodil in patients with alcohol or methamphetamine use disorder. Although the number of participants was relatively low, evidence of its safety and efficacy was found. The present review discusses the potential of GIRK channel modulators as possible medications for addiction. Therapeutic agents that target GIRK channels may be promising for the treatment of SUDs.